(untitled) (Metallurgy and Foundry Engineering, 2010)
In this paper are introduced analytical calculations of strain distribution in ECAP process in plane strain state. Analysed was friction influence on distribution and value of effective strain in channel die band. Numerical calculations were done by using of Q Form 3D commercial programme.